Overexpression of insulin-like growth factor-2 mRNA-binding protein 1 is associated with periodontal disease - Burra Anand Deepika; Jaiganesh Ramamurthy; Balachander Kannan; Vijayashree Priyadharsini Jayaseelan; Paramasivam Arumugam (Journal of Oral Biology and Craniofacial Research)
Objective: To investigate the potential role of a novel m6A RNA regulator, Insulin-like Growth Factor-2 mRNA-binding protein 1 (IGF2BP1), in periodontal disease pathogenesis. Materials and methods: Gingival tissue samples from 60 periodontitis patients and 60 healthy individuals were analyzed for IGF2BP1 mRNA and protein expression via real-time quantitative PCR (RT-qPCR) and Western blotting. Additionally, Porphyromonas gingivalis Lipopolysaccharide (Pg-LPS) -induced human gingival fibroblasts (HGFs) were evaluated for IGF2BP1 and proinflammatory cytokine expression. In silico functional analysis further explored potential molecular mechanisms. Results: IGF2BP1 mRNA and protein levels were significantly higher in the periodontitis group compared to the healthy group. Functional analysis implicated IGF2BP1 in regulating the IL-17 signaling pathway, a key player in inflammation. Pg-LPS treatment upregulated IGF2BP1 and proinflammatory cytokines in HGFs, supporting this finding. Conclusion: Our study suggests that IGF2BP1 overexpression contributes to periodontitis pathogenesis, potentially through IL-17 signaling. Further research is needed to elucidate the precise molecular mechanisms and explore IGF2BP1 as a potential therapeutic target or biomarker for this common oral disease.